Problem-Based Learning Model in Elementary School Students: Learning Activity and Learning Outcomes - Krisdianto, Indun; Sudarmiani, Sudarmiani; Nugraha, Nurhadji (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study investigates the effectiveness of the Problem-Based Learning (PBL) model in improving learning activity and learning outcomes of elementary school students in IPAS (Science and Social Studies) learning within the context of the Merdeka Curriculum implementation. Methodology: A quantitative approach was employed using a quasi-experimental posttest non-equivalent control group design. The participants consisted of 22 third-grade students at SDN 02 Nambangan Lor, Madiun City, divided into an experimental class (n = 11) taught using the PBL model and a control class (n = 11) taught using a traditional learning model. Data were collected through learning activity observation sheets and learning outcome tests, then analyzed using descriptive statistics and independent sample t-tests with a significance level of 0.05. Main Findings: The results show that students in the experimental class demonstrated significantly higher learning activity and learning outcomes compared to those in the control class. The independent sample t-test revealed a significant difference in learning activity (t = 4.129, p < 0.05) and learning outcomes (t = 5.744, p < 0.05) between the two groups. These findings indicate that the PBL model is more effective than traditional learning in fostering active student participation and improving academic achievement. Novelty/Originality of this study: This study provides empirical evidence supporting the integration of Problem-Based Learning as an instructional strategy to enhance the quality of IPAS learning in elementary schools, particularly in alignment with the student-centered principles of the Merdeka Curriculum.